2017
DOI: 10.1002/celc.201700211
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Iron Alloy Nanoparticle‐Decorated K2NiF4‐Type Oxide as an Efficient and Sulfur‐Tolerant Anode for Solid Oxide Fuel Cells

Abstract: We report a new nickel‐iron alloy nanoparticle‐decorated LaSrFe0.75Ni0.25O4 K2NiF4‐type oxide with Ruddlesden‐Popper structure (RP‐LSFN), which performed as a high‐performance sulfur‐resistant anode prepared by using an infiltration method for solid oxide fuel cells (SOFCs) with LaSrFeNiO6‐δ double perovskite (DP‐LSFN) as the precursor. A reduction converts the DP‐LSFN phase into mixed phases containing the RP‐LSFN and FeNi3 nanoparticles. The morphology, thermal expansion behavior, sulfur tolerance, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 56 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, a phenomenon called exsolution or precipitation of NPs has been recently observed at the surface of perovskite oxides. [208][209][210][211] Interestingly, the NPs are particularly active for electrocatalytic reactions at room temperature such as ORR, OER and hydrogen evolution reaction (HER). [210,211] The application of exsolution phenomenon in perovskitebased CEs for DSSCs should be an attractive future research direction.…”
Section: Conclusion Challenges and Perspectivesmentioning
confidence: 99%
“…Furthermore, a phenomenon called exsolution or precipitation of NPs has been recently observed at the surface of perovskite oxides. [208][209][210][211] Interestingly, the NPs are particularly active for electrocatalytic reactions at room temperature such as ORR, OER and hydrogen evolution reaction (HER). [210,211] The application of exsolution phenomenon in perovskitebased CEs for DSSCs should be an attractive future research direction.…”
Section: Conclusion Challenges and Perspectivesmentioning
confidence: 99%
“…With the advancing of exsolution strategies, many other exsolved products, aside from B‐site single metal nanoparticles, have been generated. These include single metals (e.g., Ag) and lanthanide oxides (e.g., PrO x ) exsolved from the A site, metal alloys (e.g., FeNi 3 and Pt 3 Ni), transition metal oxides (e.g., MnO), metal/metal oxide hybrids (e.g., Co/CoO x ) exsolved from the B site, and metal oxides/metal composites (e.g., BaO and Ni) exsolved from both the A and B sites. The parent perovskite oxides used for exsolution can be synthesized not only by conventional methods such as solid‐state reaction or sol–gel process, but also by newly developed approaches like electrospinning and template‐assisted synthesis .…”
Section: Synthetic Methods Of Nanostructured Perovskitesmentioning
confidence: 99%
“…Exsolution : Besides infiltration, exsolution is also extensively used to develop nanoparticle‐decorated perovskite anodes. It is interesting that nanoparticles can lead to the enhancement in catalytic activity because of the high chemical reactivity conferred to the parent perovskite materials . For instance, Ni nanoparticles were exsolved from La 0.8 Sr 0.2 Cr 0.69 Ni 0.31 O 3− δ after a reducing treatment in H 2 , which extended the length of triple phase boundaries (TPB) and thus contributed to the improvement in the SOFC performance .…”
Section: Nanostructured Perovskites For Electrocatalysis‐based Energymentioning
confidence: 99%
“…[25,26] To obtain this structure at low temperatures, a recently proposed method is to reduce the perovskite derivatives at temperatures near 800 C, resulting in the formation of the Ruddlesden-Popper structure along with in situ grown metallic-phase nanoparticles. [15,17,[27][28][29][30] This strategy ensures that particle growth of the Ruddlesden-Popper support, which leads to a decrease in reaction sites, is suppressed due to the relatively low preparation temperature. It has been previously reported that the Ruddlesden-Popper material of La gas mixture at 800 C, whose condition is much milder than the typical synthesis method of Ruddlesden-Popper materials.…”
Section: Introductionmentioning
confidence: 99%